meer voorbeelden


Opdracht 1

Los exact op:

  1. $2\sin \left( {4t} \right) - 3 =  - 4$
  2. $\cos ^2 \left( {2t} \right) = \frac{1}{2}$
  3. $\sin \left( {2t + \pi } \right) \cdot \cos \left( {3t- \pi } \right) = 0$
  4. $\eqalign{\sin \left( {\frac{1}{4}\pi x} \right) = \sin \left( {\frac{1}{4}\pi } \right)}$

Uitwerkingen

a. $
\eqalign{
  & 2\sin \left( {4t} \right) - 3 =  - 4  \cr
  & 2\sin \left( {4t} \right) =  - 1  \cr
  & \sin \left( {4t} \right) =  - \frac{1}
{2}  \cr
  & 4t =  - \frac{1}
{6}\pi  + k \cdot 2\pi  \vee 4t = 1\frac{1}
{6}\pi  + k \cdot 2\pi   \cr
  & 4t = 1\frac{5}
{6}\pi  + k \cdot 2\pi  \vee 4t = 1\frac{1}
{6}\pi  + k \cdot 2\pi   \cr
  & t = \frac{{11}}
{{24}}\pi  + k \cdot \frac{1}
{4}\pi  \vee t = \frac{7}
{{24}}\pi  + k \cdot \frac{1}
{2}\pi  \cr}
$
b. $
\eqalign{
  & \cos ^2 \left( {2t} \right) = \frac{1}
{2}  \cr
  & \cos \left( {2t} \right) =  - \sqrt {\frac{1}
{2}}  \vee \cos \left( {2t} \right) = \sqrt {\frac{1}
{2}}   \cr
  & \cos \left( {2t} \right) =  - \frac{1}
{2}\sqrt 2  \vee \cos \left( {2t} \right) = \frac{1}
{2}\sqrt 2   \cr
  & 2t = \frac{3}
{4}\pi  + k \cdot 2\pi  \vee 2t = 1\frac{1}
{4}\pi  + k \cdot 2\pi  \vee 2t = \frac{1}
{4}\pi  + k \cdot 2\pi  \vee 2t = 1\frac{3}
{4}\pi  + k \cdot 2\pi   \cr
  & t = \frac{3}
{8}\pi  + k \cdot \pi  \vee t = \frac{5}
{8}\pi  + k \cdot \pi  \vee t = \frac{1}
{8}\pi  + k \cdot \pi  \vee t = \frac{7}
{8}\pi  + k \cdot \pi   \cr
  & t = \frac{1}
{8}\pi  + k \cdot \frac{1}
{4}\pi  \cr}
$
c.

$
\eqalign{
  & \sin \left( {2t + \pi } \right) \cdot \cos \left( {3t - \pi } \right) = 0  \cr
  & \sin (2t + \pi ) = 0 \vee \cos (3t - \pi ) = 0  \cr
  & 2t + \pi  = k \cdot \pi  \vee 3t - \pi  = \frac{1}
{2}\pi  + k \cdot \pi   \cr
  & 2t = k \cdot \pi  \vee 3t = 1\frac{1}
{2}\pi  + k \cdot \pi   \cr
  & t = k \cdot \frac{1}
{2}\pi  \vee t = \frac{1}
{2}\pi  + k \cdot \frac{1}
{3}\pi  \cr}
$

Naschrift
Bij de oplossing hierboven zitten nog een aantal dubbelen...

d. $
\eqalign{
  & \sin \left( {\frac{1}
{4}\pi t} \right) = \sin \left( {\frac{1}
{4}\pi } \right)  \cr
  & \frac{1}
{4}\pi t = \frac{1}
{4}\pi  + k \cdot 2\pi  \vee \frac{1}
{4}\pi t = \frac{3}
{4}\pi  + k \cdot 2\pi   \cr
  & \pi t = \pi  + k \cdot 8\pi  \vee \pi t = 3\pi  + k \cdot 8\pi   \cr
  & t = 1 + k \cdot 8 \vee t = 3 + k \cdot 8 \cr}
$

©2004-2021 W.v.Ravenstein